Renoprotective effect and mechanism of polysaccharide from Polyporus umbellatus sclerotia on renal fibrosis. (15th May 2019) - Li, Hailun; Yan, Zhuan; Xiong, Qingping; Chen, Xiaoling; Lin, Yongtao; Xu, Yong; Bai, Lin; Jiang, Wei; Zheng, Donghui; Xing, Changying
Highlights: Polysaccharide (PPUS) from Polyporus umbellatus sclerotia had renoprotective effect. PPUS had a noticeable protective effects on renal interstitial fibrosis. The mechanism of PPUS treat renal fibrosis might be inhibit inflammation. Mechanism of PPUS treat renal fibrosis was inhibit epithelial-mesenchymal transition. Mechanism of PPUS treat renal fibrosis was rebalance of fibrotic/antifibrotic factor. Abstract: As a fungal polysaccharide, polysaccharide (PPUS) from Polyporus umbellatus sclerotia have showed remarkable anti-inflammatory activities. In view of the closely relationship between inflammation and renal fibrosis, and considering the significant role of other fungal polysaccharides on treatment of renal fibrosis, we speculated that PPUS may have therapeutic effects on renal fibrosis. However, there was not any reports about PPUS treatment this disease. The purpose of this paper is to investigate renoprotective effect and mechanism of PPUS on renal fibrosis. The results indicated that PPUS can improve renal function and ameliorate the degree of renal collagen deposition and further fibrosis. Its mechanism was found to be related with decreased inflammation, suppressive epithelial-mesenchymal transition, reconstructed the balance of matrix metalloproteinases and tissue inhibitor of metalloproteinases, and pro-fibrotic and anti-fibrotic factors. The data implied that PPUS can serve as a clinical candidate on treatment of renal interstitial fibrosis.